Preliminary study for the development of a model of management innovation in universities: Application in the Technological Institute of Costa Rica - Carvajal-Morales, Juan Carlos (2014)
Innovation is the process by which some benefit is obtained from knowledge by producing new and significantly improved products, services or processes introduced in the society (MEIC, 2010). Quoted by (Orozco. P, 2013) In this context, the academy is the appropriate environment to encourage ideas generation oriented to their introduction and commercialization in the market place. However, despite the Costa Rica Institute of Technology as a university has established mechanisms in its regulation and in its administrative and academic structure , there is no a clear model for innovation management. The “Proposal for a validated model of innovation management in universities: Practical application at Costa Rica Institute of Technology “ project, aims to develop and validate a model to clearly guide teachers, researchers and students in the innovation adventure. In the first stage of the project, information about the main sources of innovation in the Costa Rica Institute of Technology as well as about best practices developed by other universities was collected. Finally, the analysis of the institutional regulation on the topic of innovation, allows to conclude that there does not exist a regulation or a clear policy that supports the faculty, the students and the administrative staff in the process of innovation.